### Derivation of Planck's Radiation Law

Derivation: Let $N$ be the total number of Planck’s oscillators and $E$ be their total energy, then the average energy per Planck’s oscillator is

$\overline{E}=\frac{E_{N}}{N} \qquad (1)$

Let there be $N_{0}, N_{1} ,N_{2} ,N_{3},---N_{n}$ oscillator having energy $E_{0}, E_{1}, E_{2}, -- E_{n}$ respectively.

According to Maxwell’s distribution, the number of oscillators in the $n^{th}$ energy state is related to the number of oscillators in the ground state by

$N_{n}=N _{0} e^{\tfrac{-nh\nu }{kt} }\qquad (2)$

Where $n$ is a positive integer. So put $n= 1,2,3,…….$. The above equation can be written for different energy states. i.e.

$N_{1}= N _{0} e^{\tfrac{-h\nu }{kt} }$

$N_{2}= N _{0} e^{\tfrac{-2h\nu }{kt} }$

$N_{3}= N _{0} e^{\tfrac{-3h\nu }{kt} }$

$.............$

$.............$

So, the total number of Planck’s Oscillators –

$N= N _{0} +N_{1}+N_{2}+N_{3}+.... N_{n}$

$N= N _{0} + N_{0} e^{\tfrac{-h\nu }{kt}}+ N_{0} e^{\tfrac{-2h\nu }{kt}}+...+ N_{0}e^{\tfrac{-nh\nu }{kt}}$

$N= N _{0}[1+e^{\tfrac{-h\nu }{kt}}+e^{\tfrac{-2h\nu }{kt}}+.... e^{\tfrac{-nh\nu }{kt}}] \qquad(3)$

Let $x = e^{\frac{-h\nu }{kt}} \qquad (4)$

Then $N = N_{0}[1+x+x^{2}+x^{3}+...+ x^{n}]$

$N = \frac{N_{0}}{1-x} \qquad(5)$ [ from Binomial theorem]

Now the total energy of oscillators –

$E_{N} = E_{0}N_{0}+ E_{1}N_{1}+ E_{2}N_{2}+...+ E_{n}N_{n}$

$E_{N } = 0.N_{0}+ h\nu N_{0} e^{\tfrac{-h\nu }{kt}}+...+nh\nu N_{0} e^{\tfrac{-nh\nu }{kt}}$

$E_{N } = N_{0}h\nu (e^{\tfrac{-h\nu }{kt}}+2e^{\tfrac{-2h\nu }{kt}}+...+ ne^{\tfrac{-nh\nu }{kt}})$

From equation $(4)$ put $x = e^{\tfrac{-h\nu }{kt}}$ in above equation. i.e

$E_{N } = N_{0}h\nu (x+2x^{2}+3x^{3}+...+nx^{n})$

$E_{N } = N_{0}h\nu x(1+2x+3x^{2}+....)$

$E_{N } = \frac{N_{0}h\nu x}{(1-x)^{2}} \qquad(6)$ (from Bionomical theorem)

Now substituting the value of $N$ from equation $(5)$ and $E_{n}$ from equation $(6)$  in equation $(1)$ –

$\overline{E}= \frac{\frac{N_{0}h\nu x}{(1-x)^{2}}}{\frac{N_{0}}{(1-x)}}$

$\overline{E}= \frac{h\nu }{(\frac{1}{x}-1)}$

$\overline{E}= \frac{h\nu }{e^{\tfrac{h\nu }{kt}}-1} \qquad(7)$

The number of oscillators per unit volume in wavelength range to $( \lambda + d\lambda )$ is $\frac{8\pi }{\lambda ^{4}} d\lambda$.

The energy per unit volume $(E_{\lambda }d\lambda )$ in the wavelength range to $( \lambda +d\lambda )$ is –

$E_{\lambda}d\lambda = \frac{8\pi }{\lambda ^{4}}d\lambda \overline{E} \qquad(8)$

From equation $(7)$ and $(8)$ –

$E_{\lambda}d\lambda = \frac{8\pi }{\lambda ^{4}}d\lambda \frac{h\nu }{(e^{\tfrac{h\nu}{kt}}-1)}$

$E_{\lambda}d\lambda = \frac{8\pi hc}{\lambda ^{5}} \frac{d\lambda}{(e^{\tfrac{hc}{\lambda kt}}-1)}$

The above equation describes Planck’s radiation law and this law was able to thoroughly explain the black body radiation spectrum.

Wien’s Displacement law from Planck’s Radiation Law:

Planck’s radiation law gives the energy in wavelength region $\lambda to \lambda +d\lambda$ as –

$E_{\lambda}d \lambda = \frac{8\pi hc}{\lambda ^{5}}(\frac{1}{e^{\tfrac{hc}{\lambda kt}}-1})d\lambda \qquad(1)$

For shorter wavelength $\lambda T$ will be small and hence

$e^{\tfrac{hc}{\lambda kt}}> > 1$

Hence, for a small value of $\lambda T$ Planck’s formula reduces to -

$E_{\lambda}d \lambda = \frac{8\pi hc}{\lambda ^{5}}(\frac{1}{e^{\tfrac{hc}{\lambda kt}}}) d\lambda$

$E_{\lambda}d\lambda = \frac{8\pi hc}{\lambda ^{5}}e^{\tfrac{-hc}{\lambda kt}}d\lambda$

$E_{\lambda}d\lambda = A \lambda ^{-5} e^{\tfrac{-hc}{\lambda kt}}d\lambda$

Where $A = 8\pi hc$

The above equation is Wien’s law of energy distribution verified by Planck radiation law.

Rayleigh-Jeans law from Planck’s Radiation Law:

According to Planck’s radiation law –

$E_{\lambda}.d\lambda = \frac{8\pi hc}{\lambda ^{5}}\frac{1 }{e^{\tfrac{hc}{\lambda kt}}-1}.d\lambda$

For longer wavelength $e^{\frac{hc}{\lambda kt}}$ is small and can be expanded as-

$e^{\tfrac{hc}{\lambda kt}} = 1+\frac{hc}{\lambda kt}+\frac{1}{2!}(\frac{hc}{\lambda kt})^{2}+....$

Neglecting the higher-order term –

$e^{\tfrac{hc}{\lambda kt}} = 1+\frac{hc}{\lambda kt}$

Hence for longer wavelength, Planck’s formula reduces to –

$E_{\lambda}.d\lambda = \frac{8\pi kt}{\lambda ^{5}}[\frac{1}{1+\frac{hc}{\lambda kt}-1}]$

$E_{\lambda}.d\lambda = \frac{8\pi kt}{\lambda ^{4}}.d\lambda$

This is Rayleigh Jean’s law verified by Planck Radiation Law.

### Numerical Aperture and Acceptance Angle of the Optical Fibre

Angle of Acceptance → If incident angle of light on the core for which the incident angle on the core-cladding interface equals the critical angle then incident angle of light on the core is called the "Angle of Acceptance. Transmission of light when the incident angle is equal to the acceptance angle If the incident angle is greater than the acceptance angle i.e. $\theta_{i}>\theta_{0}$ then the angle of incidence on the core-cladding interface will be less than the critical angle due to which part of the incident light is transmitted into cladding as shown in the figure below Transmission of light when the incident angle is greater than the acceptance angle If the incident angle is less than the acceptance angle i.e. $\theta_{i}<\theta_{0}$ then the angle of incidence on the core-cladding interface will be greater than the critical angle for which total internal reflection takes place inside the core. As shown in the figure below Transmission of lig

### Fraunhofer diffraction due to a single slit

Let $S$ be a point monochromatic source of light of wavelength $\lambda$ placed at the focus of collimating lens $L_{1}$. The light beam is incident normally from $S$ on a narrow slit $AB$ of width $e$ and is diffracted from it. The diffracted beam is focused at the screen $XY$ by another converging lens $L_{2}$. The diffraction pattern having a central bright band followed by an alternative dark and bright band of decreasing intensity on both sides is obtained. Analytical Explanation: The light from the source $S$ is incident as a plane wavefront on the slit $AB$. According to Huygens's wave theory, every point in $AB$ sends out secondary waves in all directions. The undeviated ray from $AB$ is focused at $C$ on the screen by the lens $L_{2}$ while the rays diffracted through an angle $\theta$ are focussed at point $p$ on the screen. The rays from the ends $A$ and $B$ reach $C$ in the same phase and hence the intensity is maximum. Fraunhofer diffraction due to

### Electromagnetic wave equation in free space

Maxwell's Equations: Maxwell's equation of the electromagnetic wave is a collection of four equations i.e. Gauss's law of electrostatic, Gauss's law of magnetism, Faraday's law of electromotive force, and Ampere's Circuital law. Maxwell converted the integral form of these equations into the differential form of the equations. The differential form of these equations is known as Maxwell's equations. $\overrightarrow{\nabla}. \overrightarrow{E}= \frac{\rho}{\epsilon_{0}}$ $\overrightarrow{\nabla}. \overrightarrow{B}=0$ $\overrightarrow{\nabla} \times \overrightarrow{E}=-\frac{\partial \overrightarrow{B}}{\partial t}$ $\overrightarrow{\nabla} \times \overrightarrow{B}= \mu \overrightarrow{J}$ Modified Form: $\overrightarrow{\nabla} \times \overrightarrow{B}= \mu \left(\overrightarrow{J}+ \epsilon \frac{ \partial \overrightarrow{E}}{\partial t} \right)$ For free space